PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP FINANCIAL DISTRESS DENGAN CORPORATE GOVERNANCE PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017- 2020 - Simanjuntak, Markus Doddy (Jurnal Manajemen dan Bisnis, 2022)
This study examines the Effect of Liquidity and Profitability on Financial Distress with Corporate Governance as a Moderating Variable in Basic and Chemical Industry Sector Companies listed on the Indonesia Stock Exchange for the 2017-2020 period. Research variables, independent variables: Liquidity is proxied by Current Ratio (X1), Profitability is proxied by Net Profit Margin (X2), Dependent variable (Y): Financial Distress and moderating variable (Z): Corporate Governance is proxied by board of commissioner size. Determination of the sample by purposive sampling obtained as many as 22 companies. Method of data analysis with multiple linear regression. The results of the study, the first hypothesis partially: the liquidity variable proxied by the Current Ratio has a significant effect on Financial Distress, the Profitability variable proxied by the Net Profit Margin has a significant effect on Financial Distress. Simultaneously: Current Ratio (X1) and Net Profit Margin (X2) have a significant effect on financial distress. The value of R Square shows that 34.2% of the dependent variable (financial distress) can be explained by the Current Ratio and Net Profit Margin, while the remaining 65.8% is explained by other variables not examined in this study. The second hypothesis: corporate governance is not able to moderate the relationship between the Current Ratio with financial distress and corporate governance is not able to moderate the relationship between Net Profit Margin and financial distress.